2023
DOI: 10.1007/s10726-022-09811-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Use of Blockchain Technology in Humanitarian Supply Chain: A Novel Fuzzy Large-Scale Group-DEMATEL

Abstract: Based on previous evidence, the use of blockchain for improving Supply Chains (SCs) regarding humanitarian projects has received attention over the past five years. The present study is innovative in investigating crucial parameters affecting the using of Blockchain Technology (BT) in Humanitarian Supply Chains (HSCs). More precisely, this study emphasizes parameters that affect blockchain in the HSCs and presents a new fuzzy large-scale group decision-making trial and evaluation laboratory (fuzzy large-scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Existing literature indicates that MCDM methods have been extensively used to explore the obstacles and requirements associated with implementing blockchain technology. Furthermore, studies conducted by Maden and Alptekin (2020), and Chen et al (2023) investigate the key factors influencing the adoption of blockchain technology. These studies have commonly identified decentralization, anonymity, and security as prominent factors influencing the decision to adopt blockchain technology.…”
Section: Design/methodology/approachmentioning
confidence: 99%
“…Existing literature indicates that MCDM methods have been extensively used to explore the obstacles and requirements associated with implementing blockchain technology. Furthermore, studies conducted by Maden and Alptekin (2020), and Chen et al (2023) investigate the key factors influencing the adoption of blockchain technology. These studies have commonly identified decentralization, anonymity, and security as prominent factors influencing the decision to adopt blockchain technology.…”
Section: Design/methodology/approachmentioning
confidence: 99%
“…Transitioning from theoretical frameworks to practical applications, BT exhibits promise in HSCs (Aranda et al, 2019;Baharmand and Comes, 2019;Baharmand et al, 2021;Chen et al, 2023;Coppi, 2020;Dubey et al, 2020;Dubey et al, 2022b;Hunt et al, 2022;Izadi et al, 2023;Khadke and Parkhi, 2020;Khan et al, 2021;L'Hermitte and Nair, 2020;Ozdemir et al, 2021;Patil et al, 2021;Ramadurai and Bhatia, 2019;Rodriguez-Espindola et al, 2020;Sahebi et al, 2020;Zwitter and Boisse-Despiaux, 2018). The BT's applications in HSC operations include tracking relief funding, preventing corruption and implementing smart contracts, all contributing to trust, transparency, traceability, human error risk mitigation and improving efficiency of fund distribution throughout the HSCs (Aranda et al, 2019;Baharmand et al, 2021;Dubey et al, 2020;Gorey, 2016;Hunt et al, 2022;Kenny, 2017;Kewell et al, 2017;Saad et al, 2022;Verhulst, 2018;Zwitter and Boisse-Despiaux, 2018).…”
Section: Application Of Blockchain Technology To Improve Financial Fl...mentioning
confidence: 99%
“…While there is optimism about BT's potential to enhance transparency and reduce transaction costs in HSCs, concerns regarding equity, privacy and trust need addressing (Stathakis, 2019). Scholars emphasize the importance of navigating these ethical implications alongside technological advancements (Baharmand and Comes, 2019;Chen et al, 2023;Coppi and Fast, 2019;Dubey et al, 2020;Dubey et al, 2021aDubey et al, , 2021bDubey et al, 2022aDubey et al, , 2022bHunt et al, 2022;Izadi et al, 2023;Seyedsayamdost and Vanderwal, 2020).…”
Section: Application Of Blockchain Technology To Improve Financial Fl...mentioning
confidence: 99%
See 2 more Smart Citations